Effect of Vitamin D3 on Changes in Muscle Mass in the Elderly in Nursing Homes: Double-Blind Controlled Randomized Trial - Prajna Adhityarani; Diana Sunardi; Esthika Dewiasty (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The decline in muscle mass and strength begins at the age of 30 years by 40% within 30 years, then will decrease by 40% every ten years after the age of 60 years. Loss of muscle mass and strength in older people causes weakness and reduced muscle function, which can lead to a decrease in the ability to perform activities of daily living and an increased risk of falls. In addition, older people are prone to malnutrition; this condition will be accompanied by micronutrient deficiencies both in older people who are undernourished and overnourished. Giving vitamin D3 to increase muscle mass and ability and reduce fat mass in older people also has pros and cons. So, this study aims to explore the effect of giving Vitamin D3 on changes in muscle mass in older adults. The study will also examine changes in upper arm muscle strength and evaluate the impact of Vitamin D3 on changes in muscle mass. This research is a study with an Experimental Randomised Control Trial (RCT) research design. The population was elderly who were deficient in vitamin D, while the study sample amounted to 26 control subjects and 26 action subjects. Samples are taken by consecutive sampling technique. Based on research findings, most older adults (60-69 years) suffer from vitamin D deficiency and deficiency. However, vitamin D3 supplementation increases the muscle mass of older adults in nursing homes, especially in the muscles of the upper and lower extremities. However, the supplement weakens muscle mass and causes bruising and bleeding but does not weaken arm muscle mass. Keywords: Elderly, Muscle Mass, Panti Werdha, Vitamin D3